Cross border marriages among the Muslims in Malaysia and Island of Lombok, Indonesia: an overview - Md Hashim, Noraini; Abdul Hak, Nora; Che Soh @ Yusoff, Roslina; Ahamat, Haniff; Md Said , Muhamad Helmi (2015)
Cross border marriages have received much attention in recent years, both from a theoretical perspective as well as practical concern. It is not a matter of happily ever after, but most crucially to highlight the reality when problems arise. Due to the increasing number of cross border marriages and very limited research, this paper aims to discuss the application of laws and practices of cross border marriages among the Muslims in Malaysia and Island of Lombok Indonesia. This research uses qualitative and legal doctrine. Data are obtained through informants consisted of the religious leader, customary leaders, officers from religious office as well as couples who practiced kahwin lari. The result shows that practice of Kahwin lari in Island of Lombok is part and parcel of their custom. This paper is preamble to a more detailed study of the cross border marriages which the result will be useful for further improvement of the existing legal provisions in Malaysia.